Annual review of United Nations affairs 1976 - Landskron, William A. (Dobbs Ferry, N.Y. : Oceana Publications, 1977)
Contains the proceedings of the 1st- Institute for Annual Review of United Nations Affairs, New York University, 1949-
Includes index.
Vols. for <1977-> issued in parts.
Vols. for 1949- issued by the New York University Graduate Program of Studies in United Nations and World Affairs in cooperation with the Dept. of Public Information of the United Nations.
1949-1965/66, in 1965/66.
Has occasional special supplement, 1958: Chronology of the United Nations; 1964- : Chronology and fact book of the United Nations.
Latest issue consulted: 2010/2011.
Keywords: United Nations -- Periodicals; Nations Unies -- Périodiques.; United Nations; United Nations -- Periodicals; Annuaires; Organisation des Nations unies; Verenigde Naties; Reference works; Periodicals; Reference works